2013
DOI: 10.1097/nen.0b013e3182851019
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Expression Analysis of αv Integrins in Human Gliomas Reveals Upregulation of Integrin αvβ3 as a Negative Prognostic Factor

Abstract: Integrin inhibitors targeting αv series integrins are being tested for their therapeutic potential in patients with brain tumors, but pathologic studies have been limited by lack of antibodies suitable for immunohistochemistry (IHC) on formalin-fixed, paraffin-embedded specimens. We compared the expression of αv integrins by IHC in brain tumor and normal human brain samples with gene expression data in a public database using new rabbit monoclonal antibodies against αvβ3, αvβ5, αvβ6, and αvβ8 complexes using b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 67 publications
3
42
3
Order By: Relevance
“…Targeting a v b 3 integrin in human GBM with RGD4C was performed in patients (Reardon et al, 2008). Previous studies reported that a v b 3 integrin can be expressed in up to 55% of human glioblastoma, depending on the tumor grade (Schnell et al, 2008;Schittenhelm et al, 2013). The a v b 3 expression was significantly higher in human GBMs than in low-grade gliomas and was seen on both activated endothelial cells and glial tumor cells existing within glioblastomas (Schnell et al, 2008;Schittenhelm et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting a v b 3 integrin in human GBM with RGD4C was performed in patients (Reardon et al, 2008). Previous studies reported that a v b 3 integrin can be expressed in up to 55% of human glioblastoma, depending on the tumor grade (Schnell et al, 2008;Schittenhelm et al, 2013). The a v b 3 expression was significantly higher in human GBMs than in low-grade gliomas and was seen on both activated endothelial cells and glial tumor cells existing within glioblastomas (Schnell et al, 2008;Schittenhelm et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that a v b 3 integrin can be expressed in up to 55% of human glioblastoma, depending on the tumor grade (Schnell et al, 2008;Schittenhelm et al, 2013). The a v b 3 expression was significantly higher in human GBMs than in low-grade gliomas and was seen on both activated endothelial cells and glial tumor cells existing within glioblastomas (Schnell et al, 2008;Schittenhelm et al, 2013). In contrast, a v b 3 expression is barely detectable on normal human endothelial cells (Koch, 2000;Pap et al, 2000;Van De Wiele et al, 2002;Kumar, 2003;Gamble et al, 2010) and is also not expressed on glia or neurons in normal adult cortex and cerebral white matter (Gladson & Cheresh, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression of αVβ3 in tumor cells and vessels, but not of other αV integrins, was shown to be dependent on tumor grade, and αVβ3 expression in tumor cells may have a prognostic impact [38]. We could show that silencing of all of the respective integrin subunits (αV, α3, α4, β3 and β5) sensitized glioblastoma cell lines to TMZ but the silencing of αVβ3 was the most powerful.…”
Section: Discussionmentioning
confidence: 99%
“…Co-culture strongly up-regulated the ITGA2B (integrin alpha 2 beta)-expression in ADSCs and ITGB3 (integrin beta 3) gene expression in A431-SCCs. Increased ITGB3 expression has been linked to an increase in migration and invasion, as well as a more aggressive phenotype of tumor cells, a progressed tumor grade and a poor prognosis [50,51]. …”
Section: Discussionmentioning
confidence: 99%